Regimes of Super-Eddington Accretion and Outflows in Extragalactic X-ray Binaries - Urquhart, Ryan Troy (Curtin University, 2018)
Ultraluminous X-ray sources (ULXs) represent stellar-mass binary systems accreting at extreme rates. Their observational diversity has been attributed to numerous different physical interpretations. Here we analyse multiwavelength observations of a select number of ULXs demonstrating a wide range of contrasting observable properties. We present the discovery of the first eclipsing ULXs, a detailed study of outflows, an examination of the highest accretion-rate sources, and finally, discuss how ULX observational and physical properties might be related.